The Philosophical Foundations of Humboldt's Linguistic Doctrines. - Manchester, Martin L. (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 1985)
Wilhelm von Humboldt's writings on language are a mixture of philosophical theorizing about mind and language on the one hand, and on the other hand, specialized studies of the most detailed sort of both the classical languages and languages which only in Humboldt's day were becoming known to European scholars, such as Sanskrit, Chinese, and native north and south American languages. This book endeavors to show that Humboldt's work on language is a coherent system of thought; to recapture and expose the systematic structure of assumption, hypothesis, argument and conclusion; and to assign many.